2021
DOI: 10.3390/neurosci2020007
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Game Design in the Unity Environment as an Example of the Use of Neurogaming on the Basis of Brain–Computer Interface Technology to Improve Concentration

Abstract: The article describes the practical use of Unity technology in neurogaming. For this purpose, the article describes Unity technology and brain–computer interface (BCI) technology based on the Emotiv EPOC + NeuroHeadset device. The process of creating the game world and the test results for the use of a device based on the BCI as a control interface for the created game are also presented. The game was created in the Unity graphics engine and the Visual Studio environment in C#. The game presented in the articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…According to the literature review and related research on game development for instruction and PR communication, it was found that most games are developed to create instructional media in different courses at elementary [20][21], high school [22][23], and higher education levels [24][25]. They are also used for measurement and evaluation process in each particular course, i.e., the development of pretest and post-test games [26][27] by various forms of game development and presentation, i.e., game development using online platforms through web applications and mobile applications like Wordwall [28], Kahoot [29], and Genially [30]; game development using software, e.g., Unity3D [31][32][33][34][35][36] and Unreal Engine [37][38]. According to the previous literature review and related research, Unity3D is used for game development and comparison of development capability with other software, e.g., Unreal Engine, Square Half-Life2, and Gamebryo-Oblivion.…”
Section: Game Development For Instructional Purposesmentioning
confidence: 99%
“…According to the literature review and related research on game development for instruction and PR communication, it was found that most games are developed to create instructional media in different courses at elementary [20][21], high school [22][23], and higher education levels [24][25]. They are also used for measurement and evaluation process in each particular course, i.e., the development of pretest and post-test games [26][27] by various forms of game development and presentation, i.e., game development using online platforms through web applications and mobile applications like Wordwall [28], Kahoot [29], and Genially [30]; game development using software, e.g., Unity3D [31][32][33][34][35][36] and Unreal Engine [37][38]. According to the previous literature review and related research, Unity3D is used for game development and comparison of development capability with other software, e.g., Unreal Engine, Square Half-Life2, and Gamebryo-Oblivion.…”
Section: Game Development For Instructional Purposesmentioning
confidence: 99%
“…BCI technologies have been used to solve numerous applied problems of controlling external objects in various spheres of human activity. In particular, these technologies have been effectively applied for controlling a mobile robot [ 1 ], automatic robot arm [ 2 ], artificial knee prosthesis [ 3 ], artificial hand prosthesis [ 4 ], a Mental Pool Game powered by Unity3D [ 5 ], many other video games [ 6 ], controlling a wheelchair [ 7 ], game design [ 8 ], modeling of 3D objects [ 9 ], detecting facial expressions [ 10 ], motor imagery classification [ 11 ], and imagined vowels classification [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The brain-computer interface is the technology that makes a direct contact between the brain and an external device possible. The analysis of electroencephalogram signals has its contribution in the field of BCI technology investigations [5,6]. Principles of quantitative electroencephalography (EEG) related to neurotherapy are discussed in [7].…”
Section: Introductionmentioning
confidence: 99%